2017
DOI: 10.11118/actaun201765051477
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Aggregate Stability Induced by Mineral Nitrogen Fertilizer Application

Abstract: The stability of soil aggregates is one of the most important characteristics of the soil affecting the overall soil quality and its health. In locality Březová nad Svitavou, experiment to reveal the effect of nitrogen dose on the stability of soil aggregates of Rendzina soil was carried out. The aim was to detect changes in soil aggregate stability after 4 and 5 years from the beginning of the experiment. There were tested 7 variants, prepared in triplicate. The results revealed that the stability of soil agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Fonte et al (2009) demonstrated that there was a 40% increase in the weight of the silt and clay content and a decrease in the microaggregate fraction after N addition. The decrease in aggregate stability with N addition was also reported by Brtnický et al (2017). Therefore, previous studies suggest that understanding of the response of aggregate and SOC stability to N application remains elusive.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Fonte et al (2009) demonstrated that there was a 40% increase in the weight of the silt and clay content and a decrease in the microaggregate fraction after N addition. The decrease in aggregate stability with N addition was also reported by Brtnický et al (2017). Therefore, previous studies suggest that understanding of the response of aggregate and SOC stability to N application remains elusive.…”
Section: Introductionmentioning
confidence: 67%
“…The decrease in aggregate stability with N addition was also reported by Brtnický et al . (). Therefore, previous studies suggest that understanding of the response of aggregate and SOC stability to N application remains elusive.…”
Section: Introductionmentioning
confidence: 97%
“…Especially with fertilizer applications made in the greenhouse 109 production system, significant increases in aggregate stability are obtained, but the effect of inorganic applications are less than organic applications (Herencia et al 2011). On the contrary, it has been reported in some studies that especially nitrogen fertilizer applications disrupt the soil aggregate system and cause a decrease in stability (Fonte et al 2009;Brtnicky et al 2017).…”
Section: Aggregate Stabilitymentioning
confidence: 95%